Quarter of a century of event-management evolution 2000-2024: the general and the special of existing approaches - V. A. Shelginskaya (Вестник университета, 2025)
The research purpose is to conceptualise the main stages and regularities of the development of event management theory in Russia since 2000 to the current times. The methodology includes comparative historical analysis of literature (stage 1), content analysis of data on domestic publication activity (stage 2), comparative analysis of based on foreign research data (stage 3). The first and second stages chronologically consider the development process of the event management and evolution of scientific research; identify time markers of emergence of new contexts and two key directions of the evolution (market and socio-cultural ones); substantiate the contribution of the semantic factor; establish the features of evolutionary transformations and key affected variables; demonstrate and comparatively characterise 6 approaches to management (corresponding to the evolutionary stages) and the seventh forecast direction. At the third stage a comparative characteristic of the development of the event management in scientific-theoretical and applied fields is given; two justifications for the use of the terminological system “event” (marketing and semantic ones) are presented; the features of improving the approaches to the event management (in English-speaking and non-English-speaking fields) during the similar period are characterised and then compared with the features of domestic development. The study results acquired at the third stage outline the field of further research and applications in the sphere of the event management in terms of managing the processes of social development, value-semantic communication in the socio-cultural space. As a whole, the material presented could be used as a practical guide to the selection of a management approach that corresponds to the context of application, and also indicates a possible direction for further theoretical and practical research that may ensures efficiency, competitiveness, and accelerated development